On the correlation links of some indicators used in public administration - Abdullakhanov, А.К.; Sansyzbayeva, G.N. (BUKETOV BUSINESS REVIEW, 2024)
Object: to find out whether there is a correlation between such indicators used in state and local government as indicators of children's enrollment in additional education and indicators of the proportion of juvenile delinquency. Methods: during the research process, logical and analytical approaches, general scientific, statistical and comparative methods were used. The value of the study, from our point of view, primarily lies in the formulation of the problem itself, and in the fact that for the first time in practice, a correlation between these indicators used in state and local government has been tested and identified. Findings: a certain correlation was identified between indicators of enrollment of children in additional education and indicators of the share of juvenile delinquency in the Republic of Kazakhstan over a ten-year period. Based on the indicators of the correlation coefficient, this correlation in some regions can be characterized as a strong inverse correlation and in some cases even as determinative one. Conclusions: under certain conditions, the system of additional education for children can play a very important role in the prevention of child crime. It should be noted that this problem requires further deeper and more thorough study.